Analysis of Civil Servant Discipline Control at the Education and Culture Office of Central Sulawesi Province - Haris Abd Kadir; Rukhayati; I Wayan Hendra Stiawan (Universitas Muhammadiyah Palu, 2023)
This study aims to determine and analyze the effectiveness of employee discipline supervision at the Education and Culture Office of Central Sulawesi Province. The sample for this research was 66 civil servants spread across every field in the Education and Culture Office of Central Sulawesi Province. The results showed that supervision at the Education and Culture Office of Central Sulawesi Province had been running effectively because the average total score of the variable leadership and employee discipline questionnaire was 4.2. Therefore the reports collected detail all program activities that will be carried out, those that are realized, and the budget that is used on time so that employees at the Education and Culture Office of Central Sulawesi Province have implemented Government Regulation no. 53 of 2010 concerning employee discipline. This can also be seen in entering and leaving work, honesty, thoroughness, and employees being responsible for their work.